Treatment of textile wastewaters by solar-driven advanced oxidation processes - Vítor J. P. Vilar (2011)
Heterogeneous (TiO(2)/UV, TiO(2)/H(2)O(2)/UV) and homogenous (H(2)O(2)/UV, Fe(2+)/H(2)O(2)/UV) solar advanced oxidation processes (AOPs) are proposed for the treatment of recalcitrant textile wastewater at pilot-plant scale with compound parabolic collectors (CPCs). The textile wastewater presents a lilac colour, with a maximum absorbance peak at 516 nm, high pH (pH = 11), moderate organic content (DOC = 382 mg C L(-1), COD = 1020 mg O(2) L(-1)) and high conductivity (13.6 mS cm(-1)), associated with a high concentration of chloride (4.7 g Cl(-) L(-1)). The DOC abatement is similar for the H(2)O(2)/UV and TiO(2)/UV processes, corresponding only to 30% and 36% mineralization after 190 kJ(UV) L(-1). The addition of H(2)O(2) to TiO(2)/UV system increased the initial degradation rate more than seven times, leading to 90% mineralization after exposure to 100 kJ(UV) L(-1). All the processes using H(2)O(2) contributed to an effective decolourisation, but the most efficient process for decolourisation and mineralization was the solar-photo-Fenton with an optimum catalyst concentration of 100 mg Fe(2+)L(-1), leading to 98% decolourisation and 89% mineralization after 7.2 and 49.1 kJ(UV) L(-1), respectively. According to the Zahn-Wellens test, the energy dose necessary to achieve a biodegradable effluent after the solar-photo-Fenton process with 100 mg Fe(2+)L(-1) is 12 kJ(UV) L(-1).